Implications of rituximab pharmacokinetic and pharmacodynamic alterations in various immune-mediated glomerulopathies and potential anti-CD20 therapy alternatives - Hartinger, Jan Miroslav; Kratky, Vojtech; Hruskova, Zdenka; Slanar, Ondrej; Tesar, Vladimir (Frontiers in immunology, 2022)
The specific B-cell depleting anti-CD20 monoclonal antibody rituximab (RTX) is effective in terms of the treatment of various immune-mediated glomerulopathies. The administration of RTX has been shown to be reliable and highly effective particularly in patients with ANCA-associated vasculitis, which is manifested predominantly with non-nephrotic proteinuria. Stable long-term B-cell depletion is usually readily attained in such patients using standard dosing regimens. However, in patients with nephrotic syndrome and non-selective proteinuria, the RTX pharmacokinetics is altered profoundly and RTX does not maintain high enough levels for a sufficiently long period, which may render RTX treatment ineffective. Since complement-derived cytotoxicity is one of the important modes of action of RTX, hypocomplementemia, frequently associated with systemic lupus erythematodes, may act to hamper the efficacy of RTX in the treatment of patients with lupus nephritis. This review provides a description of RTX pharmacokinetics and pharmacodynamics in several selected glomerulopathies, as well as the impact of proteinuria, anti-drug antibodies and other clinical variables on the clearance and volume of distribution of RTX. The impact of plasmapheresis and peritoneal dialysis on the clearance of RTX is also discussed in the paper. A review is provided of the potential association between pharmacokinetic and pharmacodynamic alterations in various kidney-affecting glomerular diseases, the sustainability of B-cell depletion and the clinical efficacy of RTX, with proposals for potential dosing implications. The role of therapeutic drug monitoring in treatment tailoring is also discussed, and various previously tested RTX dosing schedules are compared in terms of their clinical and laboratory treatment responses. Since alternative anti-CD20 molecules may prove effective in RTX unresponsive patients, their pharmacokinetics, pharmacodynamics and current role in the treatment of glomerulopathies are also mentioned.
Keywords: monoklonální protilátky; Antibodies, Monoclonal; rituximab; proteinurie; lidé; obinutuzumab; Humans; Proteinuria; ocrelizumab; membranous nephropathy; lupus nephritis; antigeny CD20; nemoci ledvin; ofatumumab; minimal change disease; Rituximab; Antigens, CD20; ANCA-associated vasculitis; vedolizumab; Kidney Diseases